Investigating Confined Space Asphyxias: Plastic Bag Involvement and Gas Inhalation – A Case Series and Literature Review - Sofija Saulė Kaubrytė; Sigitas Chmieliauskas; Giedrė Kažukauskė; Sigitas Laima; Diana Vasiljevaitė; Jurgita Stasiūnienė (Acta Medica Lituanica)
Background: Asphyxia within confined spaces, particularly involving plastic bag suffocation and gas inhalation, presents complex forensic challenges. This study explores mechanisms, epidemiology, and forensic considerations of these fatalities, drawing from a comprehensive literature review and analysis of four clinical cases. Plastic bag asphyxia, exacerbated by oxygen depletion and carbon dioxide accumulation, induces rapid loss of consciousness and cardiorespiratory arrest. The method’s lethality is increased when combined with inert gases like helium, known for their rapid onset of hypoxia and painless nature. Recent research demonstrates a growing incidence of plastic bag suffocation as a method of suicide. The accessibility of suicide-related information on online platforms contributes to the dissemination of new methods, posing challenges for suicide prevention efforts. Forensic investigations often face obstacles in accurately determining the cause and manner of death, with nonspecific autopsy findings and scene manipulations complicating the diagnostic process. Materials and methods: A literature research was conducted across PubMed and Google Scholar databases, focusing on articles published in the last 5 years, applying keywords relevant to the topic under consideration and their combinations. 34 pertinent articles were selected, supplemented by data from the Lithuanian State Forensic Medicine Service, involving four clinical cases of confined space asphyxia. Autopsy findings, toxicological analyses, and contextual details were thoroughly examined to determine the mechanism and circumstances of death. Results: Plastic bag suffocation, often combined with inert gas inhalation, emerges as a common method in suicides. Demographic analyses reveal distinct patterns, with younger age groups demonstrating an increased tendency for gas inhalation suicides. The accessibility and perceived painlessness of helium contribute to its rising usage for suicide purposes. Forensic challenges include nonspecific autopsy findings, manipulations of death scenes, and difficulties in detecting inert gases postmortem. Enhanced surveillance and efforts to restrict access to these tools are crucial in preventing the spread of new suicide methods. Conclusions: The study highlights the multifaceted nature of asphyxiation deaths within confined spaces and the importance of proactive interventions in suicide prevention. Enhanced surveillance, tailored prevention strategies, and collaborative efforts are essential in addressing evolving suicide methods and reducing their impact.